Associations of sarcopenia, sarcopenia parameters and motoric cognitive risk syndrome in Chinese older adults - Jiang, Dian; Chen, Xi; Huang, Jundan; Wu, Lina; Chen, Yifei; Feng, Hui; Hu, Mingyue (Frontiers in Aging Neuroscience, 2023)
Background: Motoric cognitive risk syndrome (MCR) is a pre-dementia symptom strongly predicts cognitive decline and dementia. Although advancements in elucidating the epidemiology of MCR, the evidence about the association between sarcopenia, sarcopenia parameters, and MCR remains scarce.The purpose of this study was to determine the associations between sarcopenia, sarcopenia parameters, and MCR among community-dwelling Chinese older adults.Methods: A total of 4184 community-dwelling older adults from the China Health and Retirement Longitudinal Study in the 2011 waves were included. Sarcopenia was diagnosed according to the Asian Working Group for Sarcopenia criteria. Sarcopenia parameters included handgrip strength (HGS), height-adjusted appendicular skeletal muscle mass (ASM/Ht2), and five-times sit-to-stand test time (FTSSTT). MCR was defined as subjective cognitive complaints and slow gait speed without dementia or impaired mobility. The associations between sarcopenia, sarcopenia parameters, and MCR were conducted using the logistic regression model. The restricted cubic spline with four knots were performed to determine the nonlinear and linear relationships between HGS, ASM/Ht2, FTSSTT, and MCR.The prevalence of MCR in wave 2011 of the China Health and Retirement Longitudinal Study was 11.2%. After adjustment for potential confounders, we found sarcopenia [odd ratio (OR) (95% CI): 1.70 (1.13~2.54), p=0.011], lower HGS [0.97 (0.96~0.99), p=0.001], and more FTSSTT [1.12 (1.10~1.15), p<0.001] were significantly associated with a higher risk of MCR. There was an inverse linear dose-response between HGS and MCR (p for overall=0.008, p for nonlinearity =0.776). The nonlinear relationship between FTSSTT and MCR was found (p for overall <0.001, p for nonlinearity=0.025) with FTSSTT ≥29s being associated with a higher risk of MCR. A doseresponse relationship was not found between ASM/Ht2 and MCR (p for overall =0.589).Sarcopenia, lower HGS, and higher FTSSTT are associated with MCR among older adults in China, while the latter two exhibit a dose-response relationship with MCR. It is suggested that timely identification and management of sarcopenia and its parameters may help delay the progression of cognitive impairment and promote healthy aging.